1970
DOI: 10.1037/h0029876
|View full text |Cite
|
Sign up to set email alerts
|

Counterconditioning versus relaxation in the desensitization of test anxiety.

Abstract: The hypotheses that the efficacy of systematic desensitization could be attributed to a general reduction in anxiety as a result of relaxation training, to simple extinction of nonreinforced fear responses, or to the operation of placebo factors were tested as alternatives to the Counterconditioning hypothesis. A sample of 119 high-test-anxious subjects were divided randomly into six different conditions: Systematic Desensitization, Relaxation Alone, Simulation Alone, Relaxation Simulation, Attention Control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…Other Litvak(80), and Obler and Terdliger("J0) have all found that the relaxation aspect was unnecessary. On the other hand, Laxer and Walker (78) found that only the relaxation aspect was necessary. Three researchers (*O.…”
Section: The Placebo Effectmentioning
confidence: 99%
“…Other Litvak(80), and Obler and Terdliger("J0) have all found that the relaxation aspect was unnecessary. On the other hand, Laxer and Walker (78) found that only the relaxation aspect was necessary. Three researchers (*O.…”
Section: The Placebo Effectmentioning
confidence: 99%
“…In all of these studies, dependent measures of anxiety showed improvement in treated compared with non-treated populations; however, results were by no means consistent and reports (Laxer, Quarter, Kooman and Walker, 1969;Laxer and Walker, 1970) suggest that various measures of anxiety were differentially affected, with manifest anxiety measures, usually self-reported showing the greatest change (Andrews, 1971;Johnson, Tyler, Thompson and Jones, 1971;Laxer et al, 1969) and physiologic measures somewhat less (Barabasz, 1973;Kondas, 1967). Tests of school performance documented improved marks in three of six studies (Deffenbacher, 1974;Mann and Rosenthal, 1969;Mann, 1972).…”
Section: Sub-clinical Studiesmentioning
confidence: 90%
“…Although several studies used more than one therapist (Andrews, 1971;Deffenbacher, 1974;Laxer and Walker, 1970) only two analyzed their data taking this into account (Mann and Rosenthal, 1969;Miller et al, 1972). In neither of these investigations was there a significant therapist effect on the desensitization process.…”
Section: Methodologic Considerationmentioning
confidence: 96%
See 2 more Smart Citations